COMPONENT ELEMENT OF USING WEB PLATFORMS - Kholikulov Bekzod Jovliyevich (American Journals, 2023)
In article is that the current level of development of science and technology, as well as the orientation of the world educational space for openness, massification, individualization, mobility, use of multimedia in education activate the task of creating a new type of educational focus environment is an electronic educational environment.
Keywords: Electronic, educational, environment, education, media, technology, mobility.